The spectral amplification effect of clouds to the night sky radiance in Madrid. (September 2016) - Aubé, M.; Kocifaj, M.; Zamorano, J.; Solano Lamphar, H.A.; Sanchez de Miguel, A.
Abstract: Artificial Light at Night (ALAN) may have various environmental impacts ranging from compromising the visibility of astronomical objects to the perturbation of circadian cycles in animals and humans. In the past much research has been carried out to study the impact of ALAN on the radiance of the night sky during clear sky conditions. This was mainly justified by the need for a better understanding of the behavior of ALAN propagation into the environment in order to protect world-class astronomical facilities. More recently, alongside to the threat to the natural starry sky, many issues have emerged from the biological science community. It has been shown that, nearby or inside cities, the presence of cloud cover generally acts as an amplifier for artificial sky radiance while clouds behave as attenuators for remote observers. In this paper we show the spectral behavior of the zenith sky radiance amplification factor exerted by clouds inside a city. We compare in-situ measurements made with the spectrometer SAND-4 with a numerical model applied to the specific geographical context of the Universidad Complutense de Madrid in Spain. Highlights: The night sky zenith spectral radiance amplification by clouds is determined theoretically. The night sky zenith spectral radiance amplification by clouds is determined experimentally with the SAND-4 spectrometer. The modeled cloud amplifications are consistent with the measurements in Madrid.